IJCM_184A: A Study on Impact of Addiction to Social Networking Sites on Psychological Well Being of Undergraduate Medical Students of GMC, Siddipet - Neerudu Sreenivas; Bhavani Santhoshi K; Snehika (Wolters Kluwer Medknow Publications, 2024)
Background: India is the third largest country to use social networking sites. A social networking site is a website where a user can create a profile and build a personal network that connects him/her to other users. Social networking sites are increasingly affecting the psychological health of teenagers and young adults and so found that addiction to online social networking sites has several psychiatric disorders, including depressive symptoms, anxiety, and low self-esteem. Objectives: To find out the addiction to social networking sites and assess the psychological well-being of undergraduate medical students of GMC, Siddipet Methodology: A cross-sectional study is being conducted in the Government medical college, Siddipet for two months among undergraduate medical students by universal sampling. The self-administered, pre-validated questionnaire, using Ryff's scale and Bergan scale, for psychological well- being and social networking site addiction respectively. Descriptive and inferential statistics were done in SPSS using appropriate statistical analysis. Results: A total of 806 students of various years of MBBS participated in the study, Males were 301 and females were 505 Among them, out of the total 806 students studied, the psychological well-being was found to be low in 6(0.74%) and moderate in 597(74.07%). In the present study, out of the total 806 medical students studied, 148(18.36%) were found to have social networking site addiction, out of which males were 52(35.13%) and females were 96(64.86%). Out of 148 medical students who were found to have social networking site addiction, psychological well-being was found to be low in 4(2.70%) and moderate in 111(75%) and the p value was found to be statistically significant at 0.007. When the psychological well-being was compared in students between those who had social networking site addiction and those who didn't had social networking site addiction, psychological well-being was comparatively less (0.74% vs 2.70% in Low psychological well-being and (75% vs 74.07%) and the difference was found to be statistically significant (p value = 0.007). Conclusion: A significant percentage of medical students (18.36%) were found to have addiction to social networking sites in our study because of the widespread availability of gadgets. Psychological well-being was found to be comparatively less in students who had social networking site addiction compared to those who didn't had the addiction.